Enhanced Bioconversion of Cellobiose by Industrial Saccharomyces cerevisiae Used for Cellulose Utilization - Hu, Meng-Long; Zha, Jian; He, Lin-Wei; Lv, Ya-Jin; Shen, Ming-Hua; Zhong, Cheng; Li, Bing-Zhi; Yuan, Ying-Jin (Frontiers in Microbiology, 2016)
Cellobiose accumulation and the compromised temperature for yeast fermentation are the main limiting factors of enzymatic hydrolysis process during simultaneous saccharification and fermentation. In this study, genes encoding cellobiose transporter and β-glucosidase were introduced into an industrial Saccharomyces cerevisiae strain, and evolution engineering was carried out to improve the cellobiose utilization of the engineered yeast strain. The evolved strain exhibited significantly higher cellobiose consumption rate (2.8-fold) and ethanol productivity (4.9-fold) compared with its parent strain. Besides, the evolved strain showed a high cellobiose consumption rate of 3.67 g/L/h at 34°C and 3.04 g/L/h at 38°C. Moreover, little cellobiose was accumulated during simultaneous saccharification and fermentation of Avicel using the evolved strain at 38°C, and the ethanol yield from Avicel increased by 23% from 0.34 to 0.42 g ethanol/g cellulose. Overexpression of the genes encoding cellobiose transporter and β-glucosidase accelerated cellobiose utilization, and the improvement depended on the strain background. The results proved that fast cellobiose utilization enhanced ethanol production by reducing cellobiose accumulation during simultaneous saccharification and fermentation at high temperature.